The use of eccentric strength training to enhance maximal muscle strength, explosive force (RDF) and muscular power - consequences for athletic performance - Aagaard, P. (The Open Sports Sciences Journal, 2010)
Heavy-resistance strength training results in marked increases in maximal muscle strength and power in both athletes, untrained subjects and elderly individuals. The addition of eccentric overload training (loads > 100% 1RM) appears to evoke enhanced gains in these parameters. Further, the use of plyometric training evokes marked increases in maximal muscle power. The adaptive physiological mechanisms involve changes in neuromuscular activity and alterations in muscle morphology (fiber size, fiber lengths) and muscle architecture, respectively, while changes in tendon stiffness may potentially contribute as well.